FAKTOR - FAKTOR YANG DAPAT MEMPENGARUHI PREMENSTRUASI SYNDROM PADA REMAJA PUTRI KELAS X SMK PGRI 2 KOTA JAMBI - Vevi Endriani (Universitas Baiturrahim, 2017)
Backgorund: Menstruation can be said as a natural process that will happen to teenagers, where the process of blood excretion indicating that internal organs functioning mature content.The purpose of this study was to know the factors Affectingof teenagers Premenstrual Syndrome In Class X SMK PGRI 2 Jambi About Premenstrual syndrome.Methods: The method used in this research was descriptive. Where the population in this study were all woman students of class X SMK PGRI 2 Jambi with total population 151 students and total sample 30 students. The data used in this study was the primary and secondary data. The data collected in this study wasquestionnaires. The technique of data collected was used simple random sampling. With a median analysis used in this study were univariate.Results: The results of research in getting that 18 (60.0%) of respondents have less knowledge, 7 (23.3%) of respondents have sufficient knowledge and 5 (16.7%) of respondents have a good knowledge of premenstrual syndrome in woman teenagers. As many as 18 (60.0%) of respondents have a negative attitude and 12 (40.0%) of respondents have a positive attitude about premenstrual syndrome in woman teenagers. The conclusion from the results is the importance of information and knowledge of the woman teenagers about importance of health reproductive of woman teenagers to confront of premenstrual syndrome teen behaviour.